Perbandingan Keterampilan Menggambar AutoCAD melalui Project Based Learning Berbantuan Video Tutorial dan Direct Instruction pada Siswa SMK - Azarin Nailah Nismara; Muhammad Kris Yuan Hidayatulloh; Gde Agus Yudha Prawira Adistana; Wahyu Dwi Mulyono (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
AutoCAD drawing skills are essential competencies for students in the Building Modeling and Information Design (DPIB) program. However, conventional teacher-centered instruction limits students’ active participation, resulting in less optimal practical skills. This study aimed to compare the AutoCAD drawing skills of students who learned through Project-Based Learning (PjBL) assisted by video tutorials and those who learned through Direct Instruction, as well as to describe students’ responses to the learning process. This study employed a quantitative approach with a quasi-experimental Non-equivalent Control Group Design. The participants consisted of 36 students in the experimental group and 39 students in the control group. Data were collected through performance assessments and student response questionnaires and analyzed using normality and homogeneity tests and the Mann–Whitney U test. The results showed a statistically significant difference between the experimental and control groups (p < 0.001). In addition, students showed positive responses to the learning process, with a response percentage of 85.22%. These findings indicate that students who learned through Project-Based Learning assisted by video tutorials achieved better AutoCAD drawing skills than those who learned through Direct Instruction. The study also suggests that this instructional approach has the potential to support the development of positive learning behaviors, particularly independence, responsibility, discipline, and carefulness.